The potential of cfd simulators for jet fire analysis: The usp-unesp experimental campaign - Schleder, Adriana Miralles [UNESP]; da Silva, Mariana Alves [UNESP]; Martins, Marcelo Ramos (Research Publishing Services, 2020)
The effects of hazardous materials releases represent a major threat to health and the environment; consequently, the proper forecast of such effects is essential to achieve the desired safety levels in operations around the world. One of the undesired scenarios that an accidental release of such materials may entail is the development of a jet fire. It is essential to properly model the jets fires to predict their consequences. In recent years, the interest in Computational Fluid Dynamics (CFD) tools to perform consequences analysis has increased. Thus, it is imperative to amplify the availability of experimental data in order to allow validation studies. In this paper, it is described the first stage of an experimental campaign undertaken by a joint venture between University of Sao Paulo (USP) and Sao Paulo State University (UNESP) to investigate the performance of CFD tools when analysing jet fires. This ongoing project intends to undertake a deep comparison between experimental data and simulations results in terms of radiation and temperature; here are presented the preliminary results regarding to radiation. The CFD tool used to analyse those scenarios showed potential to provide good adherence between predicted and measured values; however, it was possible to highlight some potential points of improvements in modelling.
Keywords: CFD simulations; Consequence analysis; Field test; Field tests; Jet fires; Risk analysis